PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA KEUANGAN (STUDI PADA PERUSAHAAN MANUFAKTUR YANG LISTING DI BURSA EFEK INDONESIA PERIODE 2014 s.d 2016) - Fitriatun Fitriatun; Makhdalena Makhdalena; RM. Riadi RM. Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine and analyze the effect of managerial ownership and institutional ownership on financial performance. The population of this study are all manufacuring companies listed on the Indonesia Stock Exchange for the period 2014-2016 that have data managerial ownership, institutional ownership and financial performance there were 19 companies with a total years of observation 57. Data obtained from Indonesian Capital Market Directory (ICMD) and website each company. The data analysis technique used in this research is path analysis with the help of SPSS program package. The results show that managerial ownership and institutional ownership simultan eously effect the financial performance. Partially, managerial ownership has a positive effect on financial performance and institutional ownership has a negative effect on financial performance.Keywords : Managerial Ownership, Institutional Ownership, Financial Performance